Racial variation in sex steroid hormone concentration in black and white men: a meta‐analysis. (20th March 2014) - Richard, A.; Rohrmann, S.; Zhang, L.; Eichholzer, M.; Basaria, S.; Selvin, E.; Dobs, A. S.; Kanarek, N.; Menke, A.; Nelson, W. G.; Platz, E. A.
Summary Sex steroid hormones are associated with chronic diseases and mortality with risk associations that differ between racial and ethnic groups. However, it is currently unclear whether sex steroid hormone levels differ between black and white men. The aim of this study was to assess racial variation in circulating testosterone, free testosterone, sex hormone‐binding globulin (SHBG) and estradiol levels in men. We searched PubMed for articles comparing circulating hormones in black and white men. A meta‐analysis was performed using weighted mean differences (WMD) to compare hormones levels between black and white men. Fifteen eligible studies were identified; three did not report adjusted means. After age adjustment, free testosterone levels were significantly higher in black than in white men (WMD = 4.07 pg/mL, 95% CI 1.26, 6.88). Depending on the free testosterone concentration in white men, this WMD translates into a racial difference ranging from 2.5 to 4.9%. Total testosterone (WMD = 0.10 ng/mL, 95% CI −0.02, 0.22), estradiol (WMD = 0.67 pg/mL, 95% CI −0.04, 1.38) and SHBG (WMD = −0.45 nmol/L, 95% CI −1.75, 0.85) concentrations did not differ comparing blacks with whites. After adjustment for age, black men have a modestly but significantly 2.5 to 4.9% higher free testosterone level than white men. Based on previous studies on effects of sex steroid hormones on risk of chronic diseases or mortality, this modest difference is unlikely to explain racial differences in disease risk.